2014
DOI: 10.1177/2042533313514048
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of bias resulting from two methods of self-reporting height and weight: a validation study

Abstract: ObjectivesTo contrast the validity of two modes of self-reported height and weight data.DesignSubjects’ self-reported height and weight by mailed survey without expectation of subsequent measurement. Subjects were later offered a physical exam, where they self-reported their height and weight again, just prior to measurement. Regression equations to predict actual from self-reported body mass index (BMI) were fitted for both sets of self-reported values. Residual analyses assessed bias resulting from applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 7 publications
2
26
0
2
Order By: Relevance
“…Findings of subsequent research have supported the aforementioned tendencies and indicate that they are global issues, with studies outside of the United States reporting similar issues . Furthermore, more recent evidence indicates that inaccuracies vary between genders, age groups and countries . In concurrence, evidence also suggests that, while overestimation of height is stable over time, the underestimation of weight appears to be increasing, particularly among heavier individuals …”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Findings of subsequent research have supported the aforementioned tendencies and indicate that they are global issues, with studies outside of the United States reporting similar issues . Furthermore, more recent evidence indicates that inaccuracies vary between genders, age groups and countries . In concurrence, evidence also suggests that, while overestimation of height is stable over time, the underestimation of weight appears to be increasing, particularly among heavier individuals …”
Section: Introductionmentioning
confidence: 76%
“…Perhaps the most obvious is that individuals may consciously under‐ or over‐report height or weight based on social desirability, while some may be oblivious to their height or weight. Other factors that may influence accuracy include assessment methods (ie, face to face, via the phone or via electronic or paper survey), anticipation of response verification, the measurement system (imperial vs metric) and whether or not variables are assessed to the nearest whole number. With respect to imperial vs metric, measuring height to the nearest centimetre rather than inch would be expected to be more accurate due to the larger‐scale range, whereas pounds would be expected to be more accurate than kilograms.…”
Section: Introductionmentioning
confidence: 97%
“…The findings relied on self-reported data, which might not accurately capture cancer prevalence and is likely to underestimate BMI (Klein, Lee, Moss, Trentham-Dietz, & Klein, 2010; Scribani et al, 2014). Data on BMI status over treatment time was not available, and, therefore, it was not possible to examine how treatment might have affected BMI.…”
Section: Discussionmentioning
confidence: 99%
“…If investigators collect self-reported height and weight from participants separately from other study variables it could also impact accuracy [23]. Finally, bias would likely have been different if self-reported weight and height had been collected in telephone interviews [10] or mailed survey [24] rather than in-person interviews.…”
Section: Discussionmentioning
confidence: 99%